2016 Labour History Review Essay Prize Winner: 'The Co-operative Commonwealth Is the Only Answer to the Fascist Empire': Support for Republican Spain Within the British Co-operative Movement, 1936–1939. Issue 3 (December 2017) - Mason, Emily
Abstract : This article explores the support that existed for the Spanish Republic within the British Co-operative movement and asks what light this can shed on existing debates about the character of civil society and democratic engagement in the age of mass democracy. While much has been written about popular support for the Spanish Republic between 1936 and 1939, the Co-operative movement has remained somewhat in the shadows, and the movement's response to the Spanish Civil War is yet to take centre stage. Similarly, while the British Co-operative movement played an important role within inter-war civil society, engaging many newly enfranchised working-class citizens with the democratic concerns of the day, studies of Britain's inter-war civic culture have tended to focus on the middle classes, and the Co-operative movement has been overlooked. With a particular focus on the movement's journals, and on the published 'letters to the editor', which reveal how ordinary co-operators engaged with 'Spain', the article examines how co-operators framed the Spanish Civil War in reference to the wider threat of fascism to their democratic and internationalist movement. It looks at how co-operators debated the issue of non-intervention; the dilemma the war posed for many pacifists within the movement; and the objections of many Catholic co-operators to the movement's support for the Spanish Republic. Finally, it explores what co-operators did in practice at the local level in terms of raising awareness and aid. Ultimately, the article sheds light on the ways in which newly enfranchised working-class and female citizens participated in a rich democratic culture in 1930s Britain, in what was an unprecedented display of international solidarity.